Occupational Health and Safety Indicators and Under-Reporting: Case Studies in Chinese Shipping - Xue, Conghua; Tang, Lijun; Walters, David (Relations industrielles / Industrial Relations, 2019)
An index-based approach to indicate the outcome of Occupational Health and Safety management has been commonly used in the implementation of the International Safety Management Code and the operation of Occupational Health and Safety management systems in the international shipping industry. Although the index-based approach is asserted to be a convenient way to measure and quantify the outcome of Occupational Health and Safety management, it is not justified in the wider literature and further empirical research is suggested by various authors. The aim of this study is to explore the role of an index-based approach in managing Occupational Health and Safety in the shipping industry.This article investigates the effectiveness of indicators in Occupational Health and Safety management in two Chinese chemical shipping companies. A qualitative approach is applied to examine the views of seafarers on safety reporting practice. The study reveals that, although the need for reporting is understood by most of the crew members, the reporting practice is significantly affected by different factors such as the crew’s concerns for their own interests, Chinese cultural factors and management’s dominant power over the crew’s performance evaluation. The findings suggest that there is a significant gap between what is required by the rules and what really occurs in terms of safety reporting practice. The study highlights the emerging problems of using Occupational Health and Safety indicators as benchmark for measuring the outcome of Occupational Health and Safety management in Chinese shipping. The conclusion is drawn in a Chinese context, and although the findings may not be similar to other industries or the shipping industry in other countries, they provide valuable indications for re-thinking and re-shaping maritime regulatory strategies.